Quality of life in intensively treated youths with early‐onset type 1 diabetes: a population‐based survey. Issue 6 (25th November 2013) - Stahl‐Pehe, Anna; Straßburger, Klaus; Castillo, Katty; Bächle, Christina; Holl, Reinhard W; Lange, Karin; Rosenbauer, Joachim
<x xml:space="preserve">Abstract</x> Objective To evaluate factors associated with self‐reported generic, chronic‐generic, and condition‐specific quality of life (QoL) impairments in intensively treated patients with early‐onset and long‐duration type 1 diabetes. Study design A total of 840 11‐ to 21‐year‐olds with type 1 diabetes onset before 5 years of age and at least 10 years diabetes duration completed questionnaires including the generic Revised Children's Quality of Life Questionnaire (KINDL‐R), the DISABKIDS chronic‐generic module (DCGM‐12), and the DISABKIDS diabetes‐specific module with impact and treatment scales to assess QoL. Regression analyses were conducted using sociodemographic, health‐related, and diabetes‐related independent variables. Results The strongest associations were observed between QoL scores and diabetes‐specific factors, especially glycemic control and treatment satisfaction. The adjusted mean differences [regression coefficients β (standard error)] between patient groups with high risk vs. optimal glycemic control were β = −4.6 (1.1) for the KINDL‐R total score, β = −8.6 (1.5) for the DCGM‐12, β = −14.4 (1.9) for the diabetes impact score, and β = −21.1 (2.7) for the diabetes treatment score (all p < 0.001). The mean differences between patient groups with poor vs. very good treatment satisfaction were β = −5.9 (1.3) for the KINDL‐R total score, β = −8.5 (1.7) for the DCGM‐12, β = −9.4 (2.0) for the diabetes impact score, and β = −15.0 (2.9) for the diabetes treatment score (all p < 0.001). In addition, recent severe hypoglycemia and an insulin regimen without an insulin pump were negatively associated with the QoL scores. Conclusion Good glycemic control and a high level of treatment satisfaction are associated with a positive QoL in youths with early‐onset type 1 diabetes.